Parameter optimization of solar air collectors with holes on baffle and analysis of flow and heat transfer characteristics. (1st November 2018) - Hu, Jianjun; Liu, Kaitong; Ma, Long; Sun, Xishan
Highlights: Improve the thermal performance of BSAC based on the principle of wind-break wall. Opening holes on baffle can improve collector efficiency and decrease flow resistance simultaneously. Internal flow and heat transfer characteristic of BSAC with holes on baffle was numerically analyzed. The hole parameters was optimized using orthogonal numerical test. The influence of inlet flow rate and the hole size on collector efficiency is significant. Abstract: This paper aims to improve the thermal performance of baffle-type solar air collector (BSAC) by opening holes on baffle based on the principle of windbreak walls. Small jets were created when fluid flowing out of the holes, which can weaken or blow away the vortexes behind baffle avoiding the generation of hot spots, and the bypass effect caused by these holes can reduce the flow resistance simultaneously. Moreover, these small jets strengthen the mixing and flow disturbance, which can enhance the heat transfer between the airflow and absorber plate leading to efficiency improvement. In this paper, the impact of hole parameters on thermal performance of BSAC was studied by orthogonal numerical tests. The analysis of variance shows that the mutual interaction among the factors of opening hole is insignificant and the influence of inlet flow rate and the hole size on collector efficiency is significant. The optimal parameter combination under different flow rates was obtained. When the inlet flow rate is 0.0044, 0.0088, and 0.0132 kg·s −1 ·m −2, the optimal collector efficiencies is 69.63%, 81.71%, and 86.83% respectively. A numerical comparison was made between the BSAC with and without holes on baffle, which explains the reason why the improved BSAC can promote the thermal efficiency and reduce the flow resistance simultaneously, providing a theoretical basis for the performance improvement of BSAC.